Big Nate blasts off - Peirce, Lincoln; Berman, Fred; Playaway Products, LLC (Solon, Ohio : Findaway World, LLC, 2022)
After his fight with Randy Betancourt makes headlines in the school paper, Big Nate has a problem worse than detention on his hands.
Release date supplied by publisher.
Print book published: New York, NY : Balzer + Bray, an imprint of HarperCollinsPublishers, [2016].
Audiobook originally released by HarperCollins.
Issued as a Wonderbook, a pre-loaded audiobook player permanently attached to a hardcover book.
Powered by a rechargeable battery ; USB charger required for recharging.
Audiobook player has 2 modes. Read-Along mode narrates the story. Learning mode asks questions related to the story.
Keywords: Big Nate -- Juvenile fiction; Conduct of life -- Juvenile fiction; Friendship -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Children's audiobooks; Children's Wonderbook chapter read-alongs.